Optimizing Potential Residents of Sumber Padi Village, Lima Puluh Subdistrict, Batu Bara Regency to Become Pioneers in Reducing the Use of Plastic Bags - Nasution, Vivi Adryani; Ayuningtias, Niza; Nasution, Ely Hayati (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Not only the city residents whose consumption levels of plastic bags are high, but villagers also contribute to the high level of plastic bag use. This educational and outreach activity aims to provide knowledge and invite villagers of Sumber Padi village, Lima Puluh Sub-district, Batubara District to be more concerned about the environment by switching to the use of environmentally friendly cloth shopping bags (pocket bag). Forming a team that consists of villagers to be the pioneers in reducing the use of plastic bags and caring for the environment was also carried out to invite other villagers and become an example for other villages to take steps in reducing the use of plastic bags. Outreach activities are carried out using interactive lectures and persuasion methods which held online and offline from July-August 2020. The results showed that the villagers' responses are very positive. This activity opens insight and raises awareness of villagers that one way to protect the earth is to reduce the use of plastic bags and adopt an environmentally friendly lifestyle. The distribution of pocket bags and masks made of cloth also inspires villagers to later create productive home-based businesses based on it. These activities also open the insight of the villagers that even though they live in the village, it does not mean they cannot think critically and become pioneers of good things.